The Role of Socioeconomic Status in the Development of Arterial Hypertension in HIV-Infected Population (Texas Journal of Medical Science, 2023)
Development of a more advanced model for the formation of unfavorable epidemiological conditions in relation to the therapeutic continuum in the HIV-infected population, also to study and evaluate, along with behavioral risk factors, such factors as characteristics of family status, living conditions, social and educational status against the background of HIV infection